Bioprospecting mangroves: antioxidant source and habitat for the endemic Bubalus sp in Rawa Aopa Watumohai National Park, Indonesia - Septiana, Andi; Jamili,; Harlis, Wa Ode; Analuddin, Kangkuso (Malaysian Society of Applied Biology, 2016)
This study determines the antioxidant contents in mangroves leaves, and elucidates strategies feasible for the management of mangroves forest and conservation of the endemic Bubalus sp. in RAWN Park, Indonesia. The antioxidant contents including anthocyanin, alkaloid, tannin and vitamin C were determined in leaf samples of Lumnitzera racemosa, Ceriops tagal and Ceriops decandra mangrove trees grown in RAWN Park. The leaves of C. tagal contained the highest anthocyanin (0.068%) in comparison to C. decandra (0.047%) and L. racemosa (0.042%). On the contrary, alkaloid content of L. racemosa leaves (0.067%) was significantly higher than that of C. tagal (0.046%) and of C. decandra (0.048%). Similarly, the tannin content of L. racemosa leaves (29.66%) was significantly higher than C. tagal (23.53%) and C. decandra (7.11%). In addition, the vitamin C content of the L. racemosa leaves (283,11 mg/100g) was significantly higher than C. decandra (231,35 mg/100g) and C. tagal (216,82 mg/100g). The footprints of areas found in these mangroves forest, which indicated that they might be used mangrove as feeding and resting areas. The results of study imply the potentiality of mangroves in RAWN Park as antioxidant and food source of Bubalus sp. The findings of this study realized the important of mangroves as antioxidant and food sources, as well as habitat of lowland anoas. Therefore, sustainable management mangrove forests must be given priority as an important habitat for endemic animal.